ANALISIS KEPUASAN KERJA TERHADAP KINERJA KARYAWAN RESTAURANT DI HOTEL PUSAKO BUKITTINGGI Rozi Yuliani Fakultas Pariwisata, Universitas Muhammadiyah Sumatera - Yuliani, Rozi (Menara Ilmu, 2018)
Pusako Hotel Bukittinggi is a 4 star hotel (****) which is located on Soekarna Hatta StreetNo. 7, Manggis, Ganting, Mandiangin Koto Selayan Bukittinggi, West Sumatera. HotelPusako comprises of 191 guest rooms, very harmoniously designed in harmony with thebeauty of the surrounding landscape and designed with Minangkabau architecture. Types ofresearch methods used in this study is descriptive method with qualitative data describing theanalysis of satisfaction on employee performance restaurant hotel Pusako Bukittinggi.Primary data is data obtained directly from the source and Secondary data are data thatstrengthen the validity of research, obtained through literature, or data or information that ifnecessary for this research.This study used descriptive qualitative method, with the number of sample as many as 13people, were used in this study is by observation, questionnaire and documentation. This studywas conducted in January 2017 and is located in Pusako Hotel Bukittinggi. Data obtainedusing a number of instruments that constitute the questionaire and processed using variablefrequency analysis for the purposes of this study.Factors that affect employee job satisfaction are wages and salaries, working conditions,quality supervision, interpersonal relationships and corporate policies and administration.This study aimed to analyzed the analysis of satisfaction on employee performance restauranthotel pusako Bukittinggi.Keyword: satisfaction and performance